A Ticket Booking and Verification App for the Al-Wehda Stadium using Facial Recognition Technology - Al-Quadhi, Abdulqader; KHALID, SHAMSUL (Applied Information Technology And Computer Science, 2025)
Stadium entry management, especially during major events like football matches, grapples with significant challenges amid rapid technological advancement. Traditional ticket presentation methods prove inefficient and prone to security breaches, such as fake tickets, e-tickets, and unauthorized usage. This project addresses these issues by developing a booking mobile application integrated with facial recognition technology, ensuring smooth and secure stadium entry. Utilizing Flutter for the interface, Firebase for data management, and Raspberry Pi for facial recognition, the application will bolster security with features like OTP and local authentication, reducing the risk of unauthorized entry. Several functional and security tests will be conducted with regular stadium-goers. By enabling ticket booking and stadium entry via facial recognition, the app promises a seamless and secure experience, elevating the stadium’s status as a technology-driven event management leader.